Ru-catalyzed ortho-oxidative alkenylation of 2-arylbenzo[d]thiazoles in aqueous solution of anionic surfactant sodium dodecylbenzenesulfonate (SDBS). Issue 5 (2nd February 2017) - Ping, Yuanyuan; Chen, Zhaobin; Ding, Qiuping; Zheng, Qiang; Lin, Yuqing; Peng, Yiyuan
Abstract: A mild and efficient Ru-catalyzed ortho -oxidative alkenylation of 2-arylbenzo[ d ]thiazoles through twofold C-H bond functionalization in aqueous solution of anionic surfactant sodium dodecylbenzenesulfonate (SDBS) has been developed using activated olefins as coupling partner. The protocol could be carried out smoothly on a gram scale, recyclable, and applicable to 2-arylthiazoles. Graphical abstract: